Robust Primary Control of Microgrids for Parametric and Topological Uncertainties: A Quest for Resilience - Baghaee, Hamid Reza; Parizad, Ali; Shafie-Khah, Miadreza; Siano, Pierluigi; Senatore, Adolfo (IEEE, 2019)
In this paper, a robust droop-based control structure is developed in primary level of a hierarchical control scheme for robust performance and robust stability against parametric and topological uncertainties to 1) improve the robust stability and robust performance 2) resolve drawbacks of previously reported methods. Considering droop control scheme, the conventional hierarchical control structure is developed and the effectiveness of the proposed control scheme is investigated considering parametric and topological uncertainties. For the sake of drawing a picture to address how we can realize a resilient microgrid including a hierarchical control structure and providing enough robustness against mentioned uncertainties, signal disturbances, and different types of nonlinearity, some special recommendations are also provided. Finally, to prove the usefulness of the proposed controller, simulation studies are done on a microgrid which includes several distributed generation units with local loads.
Keywords: Distributed energy resources; droop control; hierarchical control; microgrid; power sharing; primary control; robust control; stability; uncertainties; fi=Sähkötekniikka|en=Electrical Engineering|